Pengaruh Intellectual Capital Terhadap Reputasi Perusahaan Dengan Menggunakan Model Komprehensif MVAIC dan Corporate Reputation Score - Novianty, Nadya (Jurnal Ilmiah Akuntansi Peradaban, 2023)
Intellectual Capital (IC) is believed to provide added value and become the most powerful factor for the company. This study aims to examine the effect of IC on corporate reputation by using a comprehensive model, modified value added (MVAIC), and corporate reputation score (CRS). The sample for this research is 38 non-cyclical consumer companies listed on the Indonesia Stock Exchange with an observation period of 2017-2021. Data analysis in this study uses Partial Least Square. The results of the study prove that intellectual capital influences a company's reputation, in more detail this research also proves that human capital efficiency, structural capital efficiency, and relational capital efficiency influence a company's reputation.